Research on Efficiency of Hybrid Power System and Optimization of Control Strategy - Hongyu Zhu; Peng Hao; Guozhi Liu; Wei Xu; Haisheng Xu (Jixie chuandong)
In order to improve the fuel economy of the power diffluence hybrid vehicle，a physical model of the hybrid system and a system control model are established. The PSO （Particle swarm optimization） with optimized initial value is used to optimize the hybrid power system efficiency. The optimal power diffluence control strategy is obtained by simulation and it is transplanted to a bus equipped with the hybrid power system and experimentally verified. The results show that the efficiency optimization algorithm can effectively improve the comprehensive system efficiency of the power system and reduce the fuel consumption of the vehicle.